Dimensi Pendidikan Agama Islam dalam Tradisi Praktik Brokohan Dan Sepasaran - Ghofur, Abdul (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
This study aims to find the dimensions of Islamic education in the practice of brokohan and market culture. This research uses descriptive qualitative research. In collecting data, the researcher uses the methods of observation, documentation, and interviews. This study found that Brokohan and Sepasaran are a form of expression of gratitude from parents for having a child, so that they are safe in the hereafter and are always given good luck in life and are always protected by God. The dimensions of Islamic education at the Brokohan and Market events are friendship, prayer, charity, gratitude and optimism.